Chemical precipitation of palm oil mill effluent (POME) - Tan, J.; T., Mohd. Rozainee; A. A., Ramlan; A. H., Mohd. Ariffin (2006)
An alternative method of treating the palm oil mill effluent (POME) within a short period without involving a vast land area is coagulation and flocculation. The four different types of coagulant combinations are aluminium sulphate, ferric chloride, ferric sulphate and ammonium sulphate with commercial polymer SR316 as flocculant were investigated as pretreatment in POME. The treatment using 10%w/w of ferric sulphate, 1% w/w of aluminium sulphate and 1% w/w of ammonium sulphate as coagulants, followed by commercial polymer SR316 as flocculant can reduce turbidity and COD at 97% and 64%, respectively. The effectiveness of coagulation and flocculation has reduced the pollutant load and eased the biological treatment system of POME.